2012
DOI: 10.1002/j.1875-9114.2012.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Antibiotic Use Due to Decreased Compliance with a Ventilator‐Associated Pneumonia Computerized Clinical Pathway: Implications for Continuing Education and Prospective Feedback

Abstract: These data highlight the importance of continued stewardship resources after CCP implementation to ensure compliance and to maximize antibiotic stewardship outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The most common clinical outcomes reported by ASP evaluations are mortality [7,8,10,18,20,22,26,30,33,35,39,46,47 [5,7,10,19,20], and clinical success/failure [24, 49, 55•]. A handful of programs were able to measure infection-attributable clinical outcomes, with respect to length of stay [6] or readmission [8, 31, 47•].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common clinical outcomes reported by ASP evaluations are mortality [7,8,10,18,20,22,26,30,33,35,39,46,47 [5,7,10,19,20], and clinical success/failure [24, 49, 55•]. A handful of programs were able to measure infection-attributable clinical outcomes, with respect to length of stay [6] or readmission [8, 31, 47•].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The definition of DOT varied between studies with some considering the administration of multiple antimicrobials in one day to represent one day of therapy [27], and others considering each additional antimicrobial given in the same day as an additional day of therapy [35, 56•]. Another common drug utilization measure was the total duration of therapy (ten studies) [6, 8, 19, 26, 39, 47•, 48, 49, 74•, 75] or duration lasting longer than a particular threshold (five studies) [26,28,29,48,77]. Other measures included antibiotic-free days [48], proportion of patients given antibiotics [32,48,49], number of antimicrobials given [33], and proportion of ICU days on antibiotics [46].…”
Section: Metrics Process Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of challenges associated with making the diagnosis of VAP, IDSA/ATS guidelines highlight the importance of reassessing patients after 48-72 hours to determine whether antibiotic therapy for VAP is needed or whether an alternative diagnosis should be pursued. Thus far, most studies have focused on optimizing appropriate antimicrobial choice for VAP; [11][12][13] however, data examining the excessive use of antibiotics for VAP in patients without VAP are limited. In 1 study, Swoboda et al 14 found that half of the empiric antibiotic use for VAP in 2 surgical ICUs was prescribed for patients without pneumonia.…”
mentioning
confidence: 99%
“…The strategy consists of improved diagnostic methods, PD optimized regimens for aminoglycosides and vancomycin, both continuous and prolonged infusion regimens in addition to providing guidance on de-escalation strategies, and duration of therapy. While this infection-based strategy reduced related morbidity, mortality, length of stay, superinfections, cost of care and improved efficacy towards high MIC pathogens, it is recognized that without a consistent implementation across the care continuum these benefits would have not been achieved [17].…”
mentioning
confidence: 99%